U-DITCH PRACETAK BERDASARKAN SNI 1725: 2016 SEBAGAI STANDAR DESAIN - Titin Sundari; Fatma Ayu Nuning Farida Afiatna (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Generally, local precast U-ditch does not yet have consistent dimensions and quality. The dimensions of the u-ditch are too large or too small with low power, making the u-ditch inefficient. This is because there is no design standard for U-ditch. This study aims to determine the strength of local precast U-ditch based on SNI 1725: 2016. The results of this analysis show that the flexural resistance of local U-ditch products is smaller than the external loads (ð“ Mn < Mu).